Study on the mechanical properties of Ti-6Al-4V alloy with minimal surface structures: effects of different heat treatment temperatures - Kai Qian; Shuangyu Liu; Fulong Zhang; Guihua Hang; Bo Cui; Ziwei Guo; Qiushi Zhang; Wang Binhua (Materials Research Express, 2025)
Triply periodic minimal surface (TPMS) structures are widely used in scaffold design for biomaterials due to their excellent porous architecture and mechanical properties. This study utilized selective laser melting (SLM) to fabricate TPMS scaffold models with porosities of 50%, 60%, 70%, and 80%, based on Gyroid and Primitive unit cells. Compression tests were conducted to investigate the changes in mechanical properties of TPMS scaffolds before and after heat treatment. The mechanisms underlying these changes were elucidated through fracture morphology analysis, microstructural observation, and finite element simulation. Results indicate that Gyroid porous scaffolds exhibit superior compressive performance compared to Primitive scaffolds, with yield strength inversely related to porosity—lower porosity corresponds to higher yield strength. During compression, Primitive scaffolds exhibited a layer-by-layer stacking failure mode, whereas Gyroid scaffolds displayed a 45° shear failure mode. The Gyroid porous scaffolds showed uniform and continuous stress distribution, and heat treatment effectively relieved residual stresses, enhancing yield strength and toughness. In contrast, Primitive porous scaffolds demonstrated stress concentration regions that reach yield limits under compression, leading to fracture. Heat treatment did not alleviate these stress concentrations but instead reduced the material’s yield limit, accelerating scaffold failure.